Pengaruh Tingkat Pendidikan dan Kesehatan terhadap Produktivitas Tenaga Kerja di Provinsi Jambi - M. Zahari MS; Muhammad Syukri; Dwi Putri Budiningtyas; Naomi Valleria Hasibuan (J-MAS (Jurnal Manajemen dan Sains), 2022)
Labor productivity is a parameter of the extent to which human resources or labor are used properly to create the desired results in a process because labor is an important factor in an economy. This study aims to determine: (1) The direct influence of the level of education and health on labor productivity. (2) the partial direct effect of education level on labor productivity and health level on labor productivity. This study uses secondary data in the form of time series data consisting of Jambi Province for the period 2001-2020. The data were obtained from the Central Statistics Agency (BPS). This study used multiple linear regression analysis. Labor productivity from 2001-2020 fluctuated and tended to decline. At the education level, it can be seen that the average length of schooling in the year was fluctuating so that in 2010 it experienced a drastic decline. The level of health in 2007 experienced a very drastic decline. The results showed that: (1) The level of education and health had a significant effect on labor productivity. (2) The level of education has a positive and significant effect on labor productivity. (3) The level of health has a positive but not significant effect on labor productivity. Based on the results of this study, it is expected to provide benefits for the provincial government to take follow-up actions such as improving facilities for education and health evenly in all districts/cities in Jambi Province.